Differential roles for the Co2+/Ni2+ transporting ATPases, CtpD and CtpJ, in Mycobacterium tuberculosis virulence. Issue 1 (20th November 2013) - Raimunda, Daniel; Long, Jarukit E.; Padilla‐Benavides, Teresita; Sassetti, Christopher M.; Argüello, José M.
Summary The genome of Mycobacterium tuberculosis encodes two paralogous P1B4‐ATPases, CtpD (Rv1469) and CtpJ (Rv3743). Both proteins showed ATPase activation by Co2+ and Ni2+, and both appear to be required for metal efflux from the cell. However, using a combination of biochemical and genetic studies we found that these proteins play non‐redundant roles in virulence and metal efflux. CtpJ expression is induced by Co2+ and this protein possesses a relatively high turnover rate. A ctpJ deletion mutant accumulated Co2+, indicating that this ATPase controls cytoplasmic metal levels. In contrast, CtpD expression is induced by redox stressors and this protein displays a relatively low turnover rate. A ctpD mutant failed to accumulate metal, suggesting an alternative cellular function. ctpD is cotranscribed with two thioredoxin genes trxA (Rv1470), trxB (Rv1471), and an enoyl‐coA hydratase (Rv1472), indicating a possible role for CtpD in the metallation of these redox‐active proteins. Supporting this, in vitro metal binding assays showed that TrxA binds Co2+ and Ni2+. Mutation of ctpD, but not ctpJ, reduced bacterial fitness in the mouse lung, suggesting that redox maintenance, but not Co2+ accumulation, is important for growth in vivo.